Strategi Pengelolaan SDM untuk Menciptakan Suasana Kerja yang Kondusif di Pondok Pesantren - Jamrizal Jamrizal; Samsu Samsu; Sasmita Hasdiana; Nur Dwi Agustina (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to analyze human resource management (HRM) strategies in creating a conducive work environment at Islamic boarding schools (Pondok Pesantren). This research employs a qualitative method with a case study approach to deeply examine HRM strategies, including planning, training, development, and performance evaluation. Data were collected through in-depth interviews, participatory observations, and document analysis. The results indicate that effective HRM fosters a harmonious work environment, enhances motivation, and builds collaboration among teaching staff and administrative personnel. Key strategies include strengthening internal communication, implementing performance-based rewards, and cultivating a work culture based on pesantren values. However, the study also highlights challenges such as limited resources and resistance to change. This study recommends improving HR competencies through continuous training, formulating adaptive HRM policies, and strengthening leadership to establish a productive and conducive work atmosphere.